Hepatitis C Virus Prevalence, Medical Status Awareness and Treatment Engagement among Homeless People Who use Drugs: Results of a Street Outreach Study - Rinat Lasmanovich; Or Shaked; Ayelet Sivan; Idan Barak; Mor Nahari; Orna Mor; Helena Katchman (SAGE Publishing, 2022)
Background: Hepatitis C virus (HCV) infection is a primary health concern among people who use drugs (PWUDs). Homeless PWUDs that constitute a key population for HCV transmission remain underrepresented in many surveys. Objectives: We performed a proactive street outreach to evaluate HCV infection prevalence among homeless PWUDs in Tel Aviv, identify risk factors associated with HCV infection, awareness of disease status and linkage to care rate. Results: Thirty-eight percent of approached PWUD were willing to participate in the study. Out of 53 subjects who got tested for anti HCV by rapid test, 29 (54.72%) had a positive result, 20 of 29 anti-HCV positive (69%) patients had positive HCV PCR. Risk factors were investigated using structured questionnaires. Heroin use was reported significantly more frequently in the HCV-positive group ( P  =  .05 , CI 95%), whereas other established risk factors did not reach significance in our cohort. While 21 of 29 (72%) HCV-positive participants were aware of their condition, only 4 of 21 (19%) received treatment in the past, and 2 of 4 (50%) failed to achieve treatment goals, as assessed by HCV PCR. Conclusions: Our data indicate a high prevalence of HCV infection among homeless PWUDs. Importantly, despite relatively high awareness of HCV status in this population, we found strikingly low access to care. These findings motivate novel interventional approaches targeted at improving patient access, and compliance among homeless PWUDs, in an effort to reduce HCV transmission.